Effects of Glycoprotein IIb/IIIa Inhibitors on Platelet Function - Harder, S.; Kirchmaier, C. M.; Breddin, H. K. (Hämostaseologie, 1999)
We have studied the effect of two monoclonal antibodies against the G PI Ib/IIIa-receptor (abciximab and YM 337) on different platelet functions in healthy male volunteers. Platelet aggregation (1, 5 and 20 μM ADP), platelet adhesion, fibrinogen binding, bleeding time and platelet induced thrombin generation (PITT) were studied after an i.v. bolus of different doses of YM337 and after a bolus (0.35 mg/kg) plus 6 h infusion at different dose levels of YM337 or after a bolus of 0.25 mg/kg abciximab followed by a six hour infusion of 0,125 μg/kg/min. After 0.2 mg/kg and 0.4 mg/kg bolus of YM337 fibrinogen binding was reduced by >80%, coinciding with a prolongation of bleeding time to approx. 60 min. Platelet aggregation returned to normal within 24 h and adhesion within 48 h. Bleeding times returned to normal already 4 h after cessation of the infusion. YM337 and abciximab effectively inhibit GPIIb/IIIa mediated platelet aggregation and adhesion in volunteers. In parallel, platelet induced thrombin generation is markedly reduced. The best method to monitor treatment with GPIIb/IIIa inhibitors still has to be defined.
Keywords: Platelet aggregation inhibitors; antibodies; GPIIb/IIIa; YM337; abciximab